Website-Based Mobile Application for Ordering Food Menu through Multilevel Feedback Queue Method (A Case Study: Lembah Dempo’s Lesehan Hut and Restaurant in Metro City, Lampung Province) - Yuni Puspita Sari; Rionaldi Ali; Rahmalia Syahputri; Amelia Fitriana (Prosiding International conference on Information Technology and Business (ICITB), 2020)
Mobile technology was regarded as a main support to contribute a great impact for facilitating a lifestyle of people in many aspects e.g., tourism and culinary. Lembah Dempo’s  Lesehan Huts and Restaurants was located in Metro city and considered as one of the business entities in a culinary field. The process of ordering food menu was manually written by the waiters/waitress in the form of an ordering note which was given to the kitchen. The problem statement of this study was a loss of ordering notes given from the waiter/waitress to the kitchen which caused inappropriate queues. This website-based mobile application for ordering food menu was designed by using the multilevel feedback queue method. It generated a food order system accessed by the customers to put the food orders. The system of this application worked in accordance with the incoming queue with the notification techniques received by the kitchen so that it facilitated the chefs who worked on the food orders and improved the services. The software development method used in this study was the prototype. The programming languages used in this study were Android Studio, Java, PHP, HTML, Api Programming, and MySQL database. The Blackbox testing was carried out with 5 test components e.g, function and button tests, interface tests, loading performance and behavior tests, structural and database tests, and initiation and termination tests.Keywords: Booking, Mobile, Prototype, MySQL.